PENGARUH MOTIVASI KERJA, KEPUASAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR PDAM KABUPATEN BARITO UTARA - Noorhayati Noorhayati (Jurnal Ekonomi dan Manajemen, 2019)
ABSTRACT The purpose of this study was to analyze the effect of work motivation, job satisfaction, and work discipline on the performance of employess of the PDAM office in North Barito Regency. Data collection is done using a questionnaire. The result show that work motivation, job satisfaction, and work discipline significantly and simultaneously affect the performance of the employess of the PDAM office in North Barito Regency; while partially only job satisfaction has a significant effect on the performance of employess of the PDAM office in North Barito Regency, and then the variable that has the most dominan effect on the performance of employess of the PDAM office in North Barito Regency is the job satisfaction.